2022
DOI: 10.3233/jad-215350
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of GRADIOR: A Neuropsychological Rehabilitation Program for People with Mild Cognitive Impairment and Mild Dementia. Results of a Randomized Controlled Trial After 4 and 12 Months of Treatment

Abstract: Background: Computer-based cognitive training programs have been developed with promising results on the maintenance/improvement of cognitive performance in people with dementia. Objective: The objective was to evaluate the effectiveness of the cognitive rehabilitation program “GRADIOR” in people with mild cognitive impairment and mild dementia. Method: This study was a single-blind multicenter randomized clinical trial. Participants were recruited from hospitals/day centers. The experimental group (EG) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 66 publications
0
16
0
3
Order By: Relevance
“…Diaz Baquero et al performed an RCT study on 43 patients with MCI and mild dementia, highlighting good adherence to treatment, good acceptability, and potential efficacy of the device ( 8 ). Another RCT performed by the same authors on 89 people with MCI and dementia demonstrated the benefit of this training on several cognitive domains ( 48 ). These promising results were confirmed by Gongora Alonso et al, who observed good acceptability of the tool in patients with severe and prolonged mental illness ( 49 ).…”
Section: Resultsmentioning
confidence: 97%
“…Diaz Baquero et al performed an RCT study on 43 patients with MCI and mild dementia, highlighting good adherence to treatment, good acceptability, and potential efficacy of the device ( 8 ). Another RCT performed by the same authors on 89 people with MCI and dementia demonstrated the benefit of this training on several cognitive domains ( 48 ). These promising results were confirmed by Gongora Alonso et al, who observed good acceptability of the tool in patients with severe and prolonged mental illness ( 49 ).…”
Section: Resultsmentioning
confidence: 97%
“…In this order of ideas, our findings indicated how some executive functions (EF) such as attention, WM, numerical reasoning, and verbal fluency, evaluated by Arithmetic, Digit Symbol and LVF-R test are involved in adherence to a CCT program such as GRADIOR. Additionally, our previous study on the effectiveness of GRADIOR indicated a trend of improvement in these cognitive processes after 4 months of intervention in the EG [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carrying out this study as part of an RCT presented a series of drawbacks in (1) the process of selecting the sample of older people and (2) its maintenance throughout the 4-month CCT. The above is due to different characteristics, which could negatively influence these two scenarios, such as the following: high mortality rate of the sample, mobility alterations, emotional alterations, the stigma of the disease, the start of a pandemic, little financing, and the high cost of resources [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Modern pharmacological studies have shown that DLs in plants serve a variety of biological activities. For example, DLs in Ginkgo biloba exhibit regulatory benefits in cardiovascular diseases, 2 cerebral neurotransmitter/ receptor activities, 3 and cognitive function improvement 4 ; DLs in Daphne genkwa Sieb. et Zucc.…”
Section: Introductionmentioning
confidence: 99%